Research and advanced technology for digital libraries : 19th International Conference on Theory and Practice of Digital Libraries, TPDL 2015 Poznań, Poland, September 14-18, 2015. Proceedings /: 19th International Conference on Theory and Practice of Digital Libraries, TPDL 2015 Poznań, Poland, September 14-18, 2015. Proceedings. (2015) - Unknown
No abstract available